THE CORRELATION BETWEEN TEACHERS' STRATEGIES AND STUDENTS' WRITING ABILITY - Fajri, Nurul (Jurnal Ilmiah Pendidikan Anak (JIPA), 2017)
This research is done to find out teachers’ strategies in writing and the correlation between teachers’ strategies and students’ writing ability.  This study employs a qualitative research, where all the data are described in a systematic way based on the asserted research questions. The subject for this research was the second year students of English Department of Tarbiyah Faculty of IAIN Ar-Raniry  that consisted of 35 students. To obtain the data, the writer applied questionnaires, interview and document analysis. As a result of this research, it is found that there were good influences between teachers’ writing strategies and students’ writing ability. It could be proven from the students’ responds of questionnaires’ distribution that 88, 57 % of the students improved their writing ability. Meanwhile, 88, 57% was motivated to write and 92, 43% of them said that teachers’ strategies made them easy to generate their ideas. Besides, based on the document analysis, it is found that there were no strongly different among each class in average value; unit one was 80.7, unit three was 77 and unit four was 78. Hence, it could be said that the hypothesis of this research was proven.  Key Words: Writing Strategies, Writing.